Nierenzellkarzinom des alten und geriatrischen Patienten - Wagener, Nina (Der Urologe, 2017)
Background: Renal cell carcinoma (RCC) is a disease of older humans. Due to increased detection of tumours by ultrasound and computed tomography, the number of incidentally diagnosed RCCs has increased. These tumours are usually smaller and of lower stage. Furthermore, there is an increase of older people in the population. Objectives: Characteristics of tumour biology, prognosis, diagnostics and therapy of localized, advanced and metastatic RCC in old and geriatric patients are provided. Methods: Systematic literature review, analysis and discussion of original research articles and expert opinions. Results: The surgical treatment of RCC in old and geriatric patients requires attention to increased morbidity and mortality. Active surveillance or ablations are alternatives to surgical treatment in localized RCC. Systemic therapy in metastatic tumours exhibit analogous efficacy with slightly worse toxicity. Conclusions: RCC in old and geriatric patients requires an adaptation of classic therapeutic strategies. Management should be adjusted individually to age and comorbidities. Efficacy, risk and toxicity of all therapeutic options should be considered. A multidisciplinary approach is important for diagnosis, assessment and therapy. Recommendations should be discussed with patients and their relatives according to the individual needs, and treatment decisions should be based on patient preferences wherever possible.
Gesehen am 16.07.2018